Bibliometric analysis of research on gut microbiota in the prevention and treatment of heart failure - ZHANG Ruihang; HUO Yanming; WANG Huiqi; WU Jing; SUN Wei; YUAN Yang; WANG Shicheng; LI Wei; ZHOU Chengkun; LIU Wenze (Yixue xinzhi zazhi, 2025)
Objective To analyze the current research status, hotspots, and development trends research on the role of gut microbiota in the prevention and treatment of heart failure both domestically and internationally.Methods Relevant literatures on the prevention and treatment of heart failure by gut microbiota were retrieved from the Web of Science core collection and the CNKI database from January 2000 to August 2024.VOSviewer and CiteSpace were used to analyze the publication volume, countries of research, institutions, disciplines, authors, and keywords.Results A total of 900 articles were included, and the number of publications and citation frequency in the field of gut microbiota prevention and treatment of heart failure showed an overall upward trend. The United States dominated early research, but in recent years, China's publication volume has rapidly climbed to the top of the global rankings. The institution with the highest publication volume of English literatures was Southern Medical University in China, while the institution with the highest publication volume of Chinese literatures was Hunan University of Chinese Medicine. The research displayed interdisciplinary characteristics, covering multiple disciplines such as cardiovascular system cardiology, pharmacology pharmacy, traditional Chinese medicine, and Chinese medicine. Core researchers represented by teams such as Sandek, Anja, and Li Lin have emerged both internationally and domestically. The burst keywords have changed from "chronic heart failure" and "bacterial translocation" around 2000 to more recent terms like "supplementation" "metabolites" "Guipi Tang" and "fecal microbiota transplantation".Conclusion Research on the role of gut microbiota in the prevention and treatment of heart failure has been gaining increasing attention. Future research could focus on exploring specific microbial strains associated with heart failure, uncovering the molecular mechanisms and signaling pathways linking gut microbiota to heart failure, and developing new strategies and interventions for gut microbiota-based therapies in heart failure.